(untitled) (Palíndromo, 2022)
The article aims to suggest a significant paradigm shift taking place whitin one of the most influential theoretical models in the role of contemporary aesthetic productions and debates, namely, the notion of “relational aesthetics”, as it was conceived by the theorist and french curator Nicolas Bourriaud. It shows how in the last exhibitions curated by Bourriaud, the Anthropocene theme, that is, the new geological era in which humanity would be entering, gains a fundamental hegemony in artistic productions and aesthetic debates, and demands an expressive revision of central postulates for the consolidation of such relational aesthetics, especially with regard to the primacy of inter-human relations and the question of accelerating radicant flows.